Effectiveness of Cinema Therapy Techniques to Improve Self-Concept in Students of SMA Negeri 8 Depok - Naillah, Alisha Aufa; Refliza, Amanda Zahra Falika; Hidayat, Rizki; Damayanti, Vina Octavia (Proceeding International Conference on Religion, Science and Education, 2025)
Self-concept is an individual’s cognitive representation of himself or herself that includes judgments, feelings, and beliefs about abilities, characteristics, and values. This self-concept acts as a reference for individual achievement. Individuals with a positive self-concept tend to have a high level of self-confidence, strong intrinsic motivation, and good resilience, so they are better able to overcome challenges and achieve their life goals. In contrast, individuals with a negative self-concept often experience difficulties in regulating emotions, lack confidence in their abilities, and tend to avoid situations that are considered threatening, thus inhibiting personal growth and achieving maximum potential. Adolescents who are in the phase of change into adulthood, tend to experience a decrease in self-concept. Adolescents who experience a decrease in self-concept are characterized by lack of confidence, pessimism, and excessive fear of failure. The purpose of this study was to determine the effectiveness of cinema therapy techniques in improving self-concept in students of SMAN 8 Depok. The participants in this study amounted to 30 students, who were divided into two groups, namely the control group and the experimental group. The experimental group was given treatment in the form of a movie with a motivational genre entitled "Like Star on Earth". This movie tells the story of a talented child who is underestimated by his environment because he has dyslexia. This situation changes when there is new support from one of the teachers who helps improve his self-concept. Thus, this movie is worth giving to our experimental research subjects who have low self-concept. While no treatment was given to the control group, in order to see the difference with the treatment of the experimental group. This research uses a type of Quasi Experiment research using Two Group Pretest-Posttest Design. The data analysis used in this study was processed using SPSS 26 software. While the data analysis method used is the Mann Whitney Test. Based on the results of the analysis of the posttest scores of the experimental group and the control group, it shows a significant value of 0.033 (p < 0.05), which means that there is a difference in the level of self-concept of students after treatment. So it can be concluded that cinema therapy treatment is effective for improving self-concept in students who have low self-concept.